A Review of Balanced Scorecard Framework in Higher Education Institution (HEIs) - Fahmi Fadhl Al-Hosaini; Saudah Sofian (International Review of Management and Marketing, 2015)
Many studies have been conducted to investigate the effectives of the BSC in organisations. It is observed that many organisations adopt different perspectives suitable for their functions in line with their vison, mission and strategic themes.  Some reseachers have highlighted its relevance to Higher Education institutions. However, previous studies have not defined wich perspectives are most relevant for public HEIs, which are not for profit by nature.  Higher Educational Institutions (HEIs) are involved in  routine processes of providing tertiary education in colleges, universities, and institutes including both undergraduate and postgraduate programmes, vocational and education training. One of the aims of HEIs is to achieve results in terms of products and services for the customers and other stake holders. In this paper, we review recent studies in top journals using  the Balanced Scorecard Framework in HEIs. The paper identifies the relenvant perspectives for HEIs and presents its contextual analysis. When implemented, this can be used to monitor their performance and enable them to adjust to emerging challenges that come as a result of implementing key strategies.